Czy rzeczywiście większa będzie radość z jednego nawracającego się grzesznika niż z dziewięćdziesięciu dziewięciu sprawiedliwych (Łk 15,7)? - Piwowar, Andrzej (The Biblical Annals, 2026)
Luke 15:7, a theological summary of the parable of the lost sheep, is a pivotal New Testament text on divine mercy. It is commonly interpreted as asserting that heaven rejoices more over one repentant sinner than over ninety-nine righteous individuals who need no repentance. However, the Greek text lacks a complete comparative structure, raising questions about whether the conjunct ἤ alone suffices to support a comparative interpretation. This article investigates this issue through a detailed syntactic analysis of Luke 15:7 and evaluates arguments traditionally used to favor a comparative reading. The findings suggest that the independent use of ἤ in the verse indicates an alternative or disjunctive function (‘or’) rather than a comparative one (‘than’), challenging the traditional interpretation of the text : “In the same way there will be rejoicing in heaven over one sinner who repents or over ninety-nine righteous persons who do not need to repent.”